2021
DOI: 10.1017/s0266462321000155
|View full text |Cite
|
Sign up to set email alerts
|

The broader societal impacts of COVID-19 and the growing importance of capturing these in health economic analyses

Abstract: The rapid spread of the current COVID-19 pandemic has affected societies worldwide, leading to excess mortality, long-lasting health consequences, strained healthcare systems, and additional strains and spillover effects on other sectors outside health (i.e., intersectoral costs and benefits). In this perspective piece, we demonstrate the broader societal impacts of COVID-19 on other sectors outside the health sector and the growing importance of capturing these in health economic analyses. These broader impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 10 publications
(11 reference statements)
0
23
0
1
Order By: Relevance
“…Productivity not only concerns paid work, but also unpaid work. Even though it is less often considered in economic evaluations [ 6 ], unpaid work should also be incorporated when analysing the full societal impact of public health issues [ 7 ]. Having to work at home may have positive and negative consequences for unpaid work, and the distribution of unpaid work within a household may change [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Productivity not only concerns paid work, but also unpaid work. Even though it is less often considered in economic evaluations [ 6 ], unpaid work should also be incorporated when analysing the full societal impact of public health issues [ 7 ]. Having to work at home may have positive and negative consequences for unpaid work, and the distribution of unpaid work within a household may change [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the quality of the health care received by patients with other diseases, particularly non-communicable ones, has declined owing to the system’s focus on COVID-19. Moreover, changes in the organization of daily life due to anti-epidemic measures, such as the closing of schools, banning of gatherings, and limitation of cultural events, have led to a social depression whose effects will only be known in retrospect ( 31 ).…”
Section: Large-scale Effects Of the Pandemicmentioning
confidence: 99%
“…1,2 These impacts have included rising costs to healthcare systems, increasing mental health issues from social isolation, compounding strain on hospitals and healthcare facilities, and ongoing disruptions to the delivery of routine care. [2][3][4] During COVID-19, authorities responded quickly to implement innovative strategies to continue the delivery of health services, and telehealth was recognised as a key strategy to achieve this. Telehealth prevented COVID-19 transmission because consultations could be managed without person-to-person contact.…”
Section: Introductionmentioning
confidence: 99%